FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMANFAATAN POS PEMBINAAN TERPADU (POSBINDU) DI PUSKESMAS BATU ANAM KABUPATEN SIMALUNGUN TAHUN 2023 - Dalimunthe, Sutan Syarif Muda; Simanjuntak, Tampak Linggom; Pardede, Sujahn Anto; Sembiring, Rusdi Andreas; Simandjuntak, Prawito Nurhidayat; saragih, erika; ., frawati (Fakultas Kedokteran, Institut Kesehatan Deli Husada Deli Tua, 2024)
Non-communicable diseases are health problems with high morbidity, disability and death rates. The Integrated Development Post (Posbindu) is a program of the Community Health Center aimed at the early detection, monitoring, and follow-up of risk factors for non-communicable diseases. The low number of Posbindu visits compared to the high incidence of non-communicable diseases at the Batu Anam Health Center is the background of this research. This study aims to examine the factors associated with the utilization of the Integrated Development Post (Posbindu) at the Batu Anam Health Center. The research design employed is cross-sectional. The study population consisted of 320 individuals, with a sample size of 76. The sampling technique used was purposive sampling. The results from the bivariate analysis indicated that the variables related to Posbindu utilization were knowledge (p=0.005), attitude (p=0.036), and health worker support (p=0.000) while the variable not related to Posbindu utilization was distance traveled (p=0.933 ) and family support (p=0.505). The results of the multivariate analysis showed that the most dominant variable related to the use of Posbindu was PR of 13.642 (95% CI: 3.218-57.828) meaning that the risk of not getting the support of health workers was 13.642 times greater in the community using Posbindu compared to respondents who did not get support from health workers.